Prognostic significance of proteinuria in stroke patients treated with intravenous thrombolysis. (10th November 2016) - Gensicke, H.; Frih, A. A.; Strbian, D.; Zini, A.; Pezzini, A.; Padjen, V.; Haueter, M.; Seiffge, D. J.; Mäkitie, L.; Traenka, C.; Poli, L.; Martinez‐Majander, N.; et al.
Abstract : Background and purpose: Proteinuria and estimated glomerular filtration rate (eGFR) are indicators of renal function. Whether proteinuria better predicts outcome than eGFR in stroke patients treated with intravenous thrombolysis (IVT) remains to be determined. Methods: In this explorative multicenter IVT register based study, the presence of urine dipstick proteinuria (yes/no), reduced eGFR (<60 ml/min/1.73 m 2 ) and the coexistence of both with regard to (i) poor 3‐month outcome (modified Rankin Scale score 3–6), (ii) death within 3 months and (iii) symptomatic intracranial hemorrhage (ECASS‐II criteria) were compared. Unadjusted and adjusted odds ratios (ORs) with 95% confidence intervals were calculated. Results: Amongst 3398 patients, 881 (26.1%) had proteinuria and 623 (18.3%) reduced eGFR. Proteinuria [ORadjusted 1.65 (1.37–2.00) and ORadjusted 1.52 (1.24–1.88)] and reduced eGFR [ORadjusted 1.26 (1.01–1.57) and ORadjusted 1.34 (1.06–1.69)] were independently associated with poor functional outcome and death, respectively. After adding both renal markers to the models, proteinuria [ORadjusted+eGFR 1.59 (1.31–1.93)] still predicted poor outcome whilst reduced eGFR [ORadjusted+proteinuria 1.20 (0.96–1.50)] did not. Proteinuria was associated with symptomatic intracranial hemorrhage [ORadjusted 1.54 (1.09–2.17)] but not reduced eGFR [ORadjusted 0.96 (0.63–1.62)]. In 234 (6.9%) patients, proteinuria and reduced eGFR were coexistent. Such patients were at the highest risk of poor outcome [ORadjusted 2.16 (1.54–3.03)] and death [ORadjusted 2.55 (1.69–3.84)]. Conclusion: Proteinuria and reduced eGFR were each independently associated with poor outcome and death but the statistically strongest association appeared for proteinuria. Patients with coexistent proteinuria and reduced eGFR were at the highest risk of poor outcome and death. Abstract : Clickhere to view the accompanying paper in this issue.